Improving Voltage Profile and Reducing Network Losses by Integration of Wind Farm and Thyristor-Switched Series Capacitors - Milad Gheydi; Farshid Abdolahnejad Baroogh (International Journal of Advances in Applied Sciences, 2017)
This paper aims at improving voltage profile and reducing the losses of active and reactive powers. The impact of wind turbines on voltage profile and power losses in critical buses is evaluated. Wind turbines, reactive power resources, i.e. thyristor-switched series capacitors, are connected to the network in mentioned states. In this study different conditions are individually and simultaneously considered with/without the wind turbines and thyristor-switched series capacitors in normal states of the network. Next, voltage profile, active power, reactive power, and the network losses are dealt with in the presence/absence of wind turbines and thyristor-switched series capacitors considering a sudden fault occurred in one power line, and the simulation results are compared with each other. The results indicate that using thyristor-switched capacitors together with the wind farm can provide enough active and reactive power for the network which increases the network capacity and decreases its losses using genetic algorithms.